Integrated Transcriptomic Analysis of Liver and Muscle Tissues Reveals Candidate Genes and Pathways Regulating Intramuscular Fat Deposition in Beef Cattle - Siwei Wang; Tingting Liu; Peng Peng; Yurong Fu; Shaoqing Shi; Shuang Liang; Xi Chen; Kun Wang; Rongyan Zhou (Animals)
Intramuscular fat (IMF) content in beef cattle is a critical determinant of beef meat quality, as it positively influences juiciness, tenderness, and palatability. In China, the crossbreeding of Wagyu and Angus is a prevalent method for achieving a better marbling level. However, the molecular mechanisms governing IMF regulation in these crossbreeds remain poorly understood. To elucidate the mechanism of IMF deposition in these crossbred cattle, we conducted a comparative transcriptomic analysis of longissimus dorsi muscles and livers from cattle with divergent IMF content. RNA-seq revealed 940 and 429 differentially expressed genes (DEGs) in the liver and muscle, respectively, with 60 genes co-differentially expressed (co-DEGs) in both tissues. Functional enrichment highlighted lipid metabolism pathways including fatty acid β-oxidation, PPAR signaling, and glycerolipid metabolism. A total of eleven genes including ACAA2, ACADL, ACOX2, CPT1B, CPT2, LPL, SLC27A1, ACAT1, GK, ACOX3, and ACSM5, were screened as key candidate genes for IMF deposition. A “liver–muscle” regulatory network of IMF deposition was built to illustrate the tissues’ interaction. The reliability of the transcriptomic data was verified by quantitative reverse real-time PCR (qRT-PCR). Our findings provide novel molecular markers for increasing the IMF content and accelerating the genetic improvement of beef quality traits in crossbred cattle.